Frontier-Based Autonomous Exploration Algorithm Implementation - Uslu, Erkan; Cakmak, Furkan; Balcilar, Muhammet; Amasyali, M. Fatih; Yavuz, Sirma (IEEE, 2015)
Exploration is defined as the selection of target points that yield the biggest contribution to a specific gain function at an initially unknown environment. Exploration for autonomous mobile robots is closely related to mapping, navigation, localization and obstacle avoidance. In this study an autonomous frontier-based exploration strategy is implemented. Frontiers are defined as the border points that are calculated throughout the mapping and navigation stage between known and unknown areas. Frontier-based exploration implementation is compatible with the Robot Operating System (ROS). Also in this study the effect of different frontier target assignment approaches are comparatively analyzed by means of total path length and thereby total exploration time.
Keywords: exploration; frontier-based; Engineering; Telecommunications